Political activists' frames in times of post-politics: evidence from Kirchnerism in Argentina and Podemos in Spain - Díaz Parra, Rubén Ibán (2015)
This article studies the transformation of the frames of political activists who come from autonomous social movements in Argentina and Spain. The cases of Kirchnerism in Argentina and Podemos and the local electoral coalitions in Spain, despite all their contextual and historical differences, follow the same pattern of politicisation. They took place within a general social tendency towards post-politics, understood as the reduction of politics to technical management, without questioning the existing capitalist order. In both cases, the model of politicisation starts within an exceptional political event: the social protests of 2001 in Argentina and the mobilisations of the 15M or indignados in Spain in 2011. Drawing on participant observation and semi-structured interviews, the article examines how social actors re-adjust their frames by managing the contradictions between their previous autonomous logic of action and their new institutional roles, according to the changing economic and political context. It concludes that there has been a clear process of politicisation, materialised in the rise of new generations of political activists, but to some extent the post-political situation remains both in the exceptional political moment and in the electoral coalitions, as the core of the economic system remains unquestioned.